Cross- broder measures modification procedures, minor’s habitual residence and internal competence of Spanish courts - Peiteado Mariscal, Pilar (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
Taking as starting point a legal ruling of the Barcelona’s Provincial Court, three of the most common problems regarding cross-border measures modification procedures on parental responsibilities are analysed. The relation with the process in which the original measures were agreed, main problems deciding the minor’s habitual residence, and the Court in which the matter must be aroused when the international competence has been ascribed to Spanish jurisdictional Courts.